De-introducing the New Testament texts, worlds, methods, stories - Penner, Todd C. 1965-; Lopez, Davina C. 1975- (Chichester Wiley Blackwell, 2015)
The order ofNew Testament things: questioning methods and meanings -- Foregrounding New Testament backgrounds: contextualizing interpretation -- Objects, objectives, and objectivities: material and visual culture and New Testament studies -- Brand(ish)ing biblical scholars(hip): New Testament studies and neoliberal subjectivity -- Back to the future: concluding observations on history, method, and theory in New Testament studies
The order ofNew Testament things: questioning methods and meaningsForegrounding New Testament backgrounds: contextualizing interpretation -- Objects, objectives, and objectivities: material and visual culture and New Testament studies -- Brand(ish)ing biblical scholars(hip): New Testament studies and neoliberal subjectivity -- Back to the future: concluding observations on history, method, and theory in New Testament studies.
Keywords: Bible -- Criticism, interpretation, etc; Bible -- Historiography; Bible -- Hermeneutics